The spectral evolution of the first galaxies: III. Simulated James Webb space telescope spectra of reionization-epoch galaxies with Lyman-continuum leakage - Zackrisson, Erik; Paardekooper, Jan-Pieter (The astrophysical journal. Part 2, Letters, 2017)
Using four different suites of cosmological simulations, we generate synthetic spectra for galaxies with different Lyman-continuum escape fractions ( f esc ) at redshifts ##IMG## [http://ej.iop.org/images/0004-637X/836/1/78/apjaa58e3ieqn1.gif] $z≈ 7$ -9, in the rest-frame wavelength range relevant for the James Webb Space Telescope ( JWST ) NIRSpec instrument. By investigating the effects of realistic star formation histories and metallicity distributions on the EW(H β )- β diagram (previously proposed as a tool for identifying galaxies with very high f esc ), we find that neither of these effects are likely to jeopardize the identification of galaxies with extreme Lyman-continuum leakage. Based on our models, we expect that essentially all ##IMG## [http://ej.iop.org/images/0004-637X/836/1/78/apjaa58e3ieqn2.gif] $z≈ 7\mbox-9$ galaxies that exhibit rest-frame ##IMG## [http://ej.iop.org/images/0004-637X/836/1/78/apjaa58e3ieqn3.gif] $\mathrmEW(\rmHβ )\lesssim 30$ Å to have ##IMG## [http://ej.iop.org/images/0004-637X/836/1/78/apjaa58e3ieqn4.gif]